2022
DOI: 10.3389/fped.2021.770754
|View full text |Cite
|
Sign up to set email alerts
|

Wave Reflection and Ventriculo-Arterial Coupling in Bicuspid Aortic Valve Patients With Repaired Aortic Coarctation

Abstract: BackgroundVentriculo-arterial (VA) coupling in bicuspid aortic valve (BAV) patients can be affected by the global aortopathy characterizing BAV disease and the presence of concomitant congenital lesions such as aortic coarctation (COA). This study aimed to isolate the COA variable and use cardiovascular magnetic resonance (CMR) imaging to perform wave intensity analysis non-invasively to shed light on VA coupling changes in BAV. The primary hypothesis was that BAV patients with COA exhibit unfavorable VA coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…These studies have focused both on various cardiovascular diseases [34] and healthy individuals with varying age [35,36] using PC-MRI, which is considered the gold standard for measuring blood flow in the aorta. Our c measurements are also supported by a study that focused solely on BAV patients and reported an average c of 4.2 m/s (range: 2.5-6.3 m/s) [37]. As reported in Table 3, c differences were not significant between the two groups within the ascending and thoracic aorta.…”
Section: Discussionsupporting
confidence: 85%
“…These studies have focused both on various cardiovascular diseases [34] and healthy individuals with varying age [35,36] using PC-MRI, which is considered the gold standard for measuring blood flow in the aorta. Our c measurements are also supported by a study that focused solely on BAV patients and reported an average c of 4.2 m/s (range: 2.5-6.3 m/s) [37]. As reported in Table 3, c differences were not significant between the two groups within the ascending and thoracic aorta.…”
Section: Discussionsupporting
confidence: 85%
“…In patients with heart failure where cardiac contractility is decreased, VACr increases. Similarly, with ageing, aortic distensibility reduces and Ea increases leading to increase in VACr [12]. Increased VACr has been associated with worse outcomes (atrial brillation, transplantation or death) in several pediatric and adult studies [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that patients with CoA have decreased aortic distensibility, which can affect Ea even if controlled for hypertension [12]. Also, hypertension itself leads to a change in Ea and Ees and hence VACr.…”
Section: Introductionmentioning
confidence: 99%